Chronic Bi-Maxillary Osteomyelitis Caused by Actinomycetes in a Patient with Severe COVID-19 - López-González, Emmanuel (2023)
Osteomyelitis is defined as the inflammation of the either medullary, cortical, or cancellous bone, including nerves and blood vessels, causing necrosis and bone sequestrum formation; this condition has become a rare pathology, and odontogenic infections are considered the most frequent causal factor. This case shows a patient with bi-maxillary osteomyelitis caused by Actinomyces spp, which was worsened for severe COVID-19 infection. Patient was submitted at surgery as, amplified total bilateral maxillectomy through the surgical technique Weber-Fergusson, and prolonged use of combination of antibiotics, achieved a good recovery. Two years later follow-up, the patient no show imaging or clinical evidence of the infection of osteomyelitis. The present case shows an interesting relationship between a rare infection and its association with COVID-19.